New record and new species of lichenized fungal genus Candelariella Müll. Arg. in Antarctica - Halici, Mehmet Gökhan; Kahraman Yiğit, Merve; Bölükbaşı, Ekrem; Güllü, Mithat (Polish Polar Research, 2023)
Previously, only three Candelariella species were known from Antarctica: C. aurella, C. flava and C. vitellina. After morphologically and phylogenetically examining our collections on soil from James Ross Island, located in the north-east Antarctic Peninsula region, and Horseshoe Island, a small rocky island in Bourgeois Fjord, Marguerite Bay in the south-west Antarctic Peninsula, we describe the lichen species Candelariella ruzgarii as new to science. Sequences of the nrITS, mtSSU and RPB1 gene regions of the new species were amplified and revealed that the phylogenetic position of the new species is in the C. aurella group, which is characterised by 8-spored asci and ± granular thalli. Candelariella ruzgarii is phylogenetically most closely related to C. aurella s. lat. but differs mainly in ecology as the new species grows on soil or on terricolous lichens, whereas the latter species grows on calcareous rocks, rarely on wood. Morphologically, C. ruzgarii is very similar to C. aggregata, a Northern Hemisphere species that grows on mosses and plant debris. Apart from the different phylogenetical position, C. ruzgarii has a thicker and sometimes slightly crenulated thalline margin and somewhat shorter ascospores than C. aggregata. We also report C. plumbea for the first time from Antarctica, a species with a thick and grey thallus that was previously known from Europe and Asia.